Stimulating effect of the preparation from leuzea safflower in veterinary obstetrics - Zhdanova, I.N. (Perm Federal Research Centre Journal, 2020)
The article is devoted to the study of therapeutic effectiveness of bioinfusin obtained on the basis of safflower leuzea, in combination with an antibiotic, for mastitis in cows during intensive lactation. The analysis of published sources shows that at present, in a number of different plants, substances have been found that have a wide spectrum of action on the organism of animals and humans, capable of increasing the adaptive capacity of an organism to environmental conditions, strengthening natural resistance and immunological reactivity. First of all, such substances include phytoecdysteroids, flavonoids, vitamins and other plant metabolites. The manifestation of antioxidant, antimicrobial, anti-inflammatory wound healing properties by ecdysteroids is known. One of the main problems of obstetric pathology in dairy farming is the high incidence of mastitis in cows. Our previous studies found that with the clinical form of mastitis in lactating cows, not only local inflammatory processes occur in the mammary gland, but also decrease in the factors of general nonspecific resistance of the whole organism is noted. Research was carried out in 2019 in production conditions at the Lipovaya Gora JSC in Perm region. In the experiment, cows of the black-and-white Holsteinized breed were used. The experimental group of cows in the treatment regimen was additionally injected with the drug bioinfusin containing leuzea extract, intramuscularly at a dose of 2,5 ml / 100 kg of an animal live weight, daily, for 10 days. The second group of cows received a treatment regimen traditionally used on the farm (control). In both groups, the conditions of feeding and zoo hygiene were the same. Treatment was carried out at diagnosis. A complex method of treating cows with clinical mastitis using bioinfusin at a dose of 2,5 ml / 100 kg of animal live weight, daily, for 10 days, and also ceftonitis, provides recovery of 75% of animals. This method was developed by the Perm Research Institute of Agriculture of Perm Federal Research Centre, Ural Branch RAS. The use of an ecdysteroid-containing drug accelerates the recovery process of cows in the experimental group and allows it to be used in general schemes for the treatment of mastitis in animals.